2018
DOI: 10.1038/s41366-018-0074-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between hyperuricemia and obesity, and its association with future risk of type 2 diabetes

Abstract: These findings indicated that increased uric acid levels probably associated with obesity and type 2 diabetes, and more definite research is needed to define any role for uric acid in relation to these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 37 publications
4
59
2
Order By: Relevance
“…We observed that SUA was higher in T2DM patients with overweight/obesity group than in those with normal weight group, SUA within normal range independently related to obesity in T2DM. Consistent with our results, several previous studies have also shown the relationship between BMI and uric acid (Han et al 2018). For example, Chen et al (Chen et al 2017) also found that prevalence of obesity steadily increased across SUA quartiles in T2DM.…”
Section: Discussionsupporting
confidence: 93%
“…We observed that SUA was higher in T2DM patients with overweight/obesity group than in those with normal weight group, SUA within normal range independently related to obesity in T2DM. Consistent with our results, several previous studies have also shown the relationship between BMI and uric acid (Han et al 2018). For example, Chen et al (Chen et al 2017) also found that prevalence of obesity steadily increased across SUA quartiles in T2DM.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with those of recent studies from Japan [30][31][32] . Evidence from these studies showed that visceral fat area is significantly related to SUA level.…”
Section: Risk Factors Of Huasupporting
confidence: 94%
“…Our results are consistent with those of recent studies from Japan. [33][34][35] Evidence from these studies showed that visceral fat area is significantly related to SUA level. Upon reduction of VAT, SUA levels significantly declined.…”
Section: Risk Factors Of Huamentioning
confidence: 99%